2010
DOI: 10.1007/s00127-010-0186-2
|View full text |Cite
|
Sign up to set email alerts
|

Mental health service use and treatment adequacy for anxiety disorders in Canada

Abstract: These findings emphasize the need to improve the access to mental health services and the quality of care for individuals with anxiety disorders in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
53
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 32 publications
5
53
0
4
Order By: Relevance
“…CBT is the most consistently efficacious psychological treatment for anxiety disorders (Butler, Chapman, Forman, & Beck, 2006;Canadian Psychiatric Association, 2006;Norton & Price, 2007) and was the only recommended psychological treatment for anxiety disorders in the 2006 clinical practice guideline from the Canadian Psychiatric Association (2006). Low rates of treatment adequacy based on clinical practice guidelines have also been found in prior studies for anxiety disorders in primary care samples (Prins et al, 2010;Smolders et al, 2009;Stein et al, 2011;Stein et al, 2004;Wittchen et al, 2002) as well as epidemiological surveys (Fernán-dez et al, 2007;Roberge et al, 2011;Wang et al, 2005;Young et al, 2008). For instance, we previously observed in a Canadian epidemiological survey that 10,6% of individuals meeting criteria for panic disorder, agoraphobia, or social anxiety disorder had received a minimum of seven outpatient visits with a specialized mental health provider in the past 12 months (Roberge et al, 2011).…”
Section: Discussionmentioning
confidence: 72%
“…CBT is the most consistently efficacious psychological treatment for anxiety disorders (Butler, Chapman, Forman, & Beck, 2006;Canadian Psychiatric Association, 2006;Norton & Price, 2007) and was the only recommended psychological treatment for anxiety disorders in the 2006 clinical practice guideline from the Canadian Psychiatric Association (2006). Low rates of treatment adequacy based on clinical practice guidelines have also been found in prior studies for anxiety disorders in primary care samples (Prins et al, 2010;Smolders et al, 2009;Stein et al, 2011;Stein et al, 2004;Wittchen et al, 2002) as well as epidemiological surveys (Fernán-dez et al, 2007;Roberge et al, 2011;Wang et al, 2005;Young et al, 2008). For instance, we previously observed in a Canadian epidemiological survey that 10,6% of individuals meeting criteria for panic disorder, agoraphobia, or social anxiety disorder had received a minimum of seven outpatient visits with a specialized mental health provider in the past 12 months (Roberge et al, 2011).…”
Section: Discussionmentioning
confidence: 72%
“…Drapeau [18] found that women were more likely to use both general and psychiatric mental health services than men. Roberge [48] found that women used general medical health services more than men with no difference in specialty service use by gender. In another study, Wang [49] found that women were less likely than their male counterparts to use psychiatry services and complementary alternative medicine only, but more likely to use general medical or other mental health specialty.…”
Section: Discussionmentioning
confidence: 99%
“…la baisse de productivité, le fait de ne pas payer d'impôts). Les troubles anxieux repré-senteraient les problèmes de santé mentale dont les coûts sont les plus élevés (Roberge, Fournier, Duhoux, Nguyen et Smolders, 2011). Pour toutes ces raisons, un dépistage et une intervention précoces nous paraissent d'une importance cruciale.…”
unclassified